Kurin Enterprise : Magic Brush / Amira Hamizah Rahmat ...[et al.] - Rahmat, Amira hamizah; Ghafar, Hanif; Mohd Amin, Mohammad Amirul Mukmin; Abdul Ghafar, Nor Iskandar (2019)
Kurin Enterprise is a new company established in 2019 and have 5 partners . This company produced a devices that help in human daily lifestyle using the smart ideas and latest technology. Our main concern is to always satisfying our customer needs by selling Magic Brush to them . Magic Brush is an electrical appliance to clean clothes or shoes in easier way and effortlessly. This product is a portable device because the user can bring it everywhere. It is also water resistant so the user does not have to worry about its durability and this product is safe for children and easy cleaning.There also a few type of brush to prevent damage on the fabric or material when brushing.